Redox-mediated reactions of vinylferrocene: toward redox auxiliaries. Issue 17 (11th April 2016) - Wiles, Alan A.; Zhang, Xiaolu; Fitzpatrick, Brian; Long, De-Liang; Macgregor, Stuart A.; Cooke, Graeme
Abstract : Redox reactions have been used to transform unreactive vinylferrocene into a powerful dienophile and reactive substrate for thiol addition reactions upon conversion to its ferrocenium state. Abstract : Chemical redox reactions have been exploited to transform unreactive vinylferrocene into a powerful dienophile for the Diels–Alder reaction and reactive substrate for thiol addition reactions upon conversion to its ferrocenium state. We have further investigated the ability of these reactions to facilitate redox-auxiliary-like reactivity by further hydrogenolyisis of the Diels–Alder adduct to the corresponding cyclopentane derivative.